Hypoxic stress tolerance of the blind subterranean mole rat: Expression of erythropoietin and hypoxia-inducible factor 1α - Shams, Imad (National Academy of Sciences, 2004)
Blind subterranean mole rats (Spalax, Spalacidae) evolved adaptive strategies to cope with hypoxia that climaxes during winter floods in their burrows. By using real-time PCR, we compared gene expression of erythropoietin (Epo), a key regulator of circulating erythrocytes, and hypoxia-inducible factor 1α (HIF-1α), Epo expression inducer, in the kidneys of Spalax and white rats, Rattus norvegicus. Our results show significantly higher, quicker, and longer responses to different O(2) levels in Spalax compared with Rattus. (i) In normoxia, both Spalax and Rattus kidneys produce small amounts of Epo. Maximal expression of Rattus Epo is noticed after a 4-h hypoxia at 6% O(2). Under these conditions, Spalax Epo levels are 3-fold higher than in Rattus. After 24 h of 10% O(2), Spalax Epo reaches its maximal expression, remarkably 6-fold higher than the maximum in Rattus; (ii) the HIF-1α level in normoxia is 2-fold higher in Spalax than in Rattus. Spalax HIF-1α achieves maximal expression after 4-h hypoxia at 3% O(2), a 2-fold increase compared with normoxia, whereas no significant change was detected in Rattus HIF-1α at any of the conditions studied; (iii) at 6% O(2) for 10 h, in which Rattus cannot survive, Epo and HIF-1α levels in Spalax galili, living in heavily flooded soils, are higher than in Spalax judaei, residing in light aerated soil. We suggest that this pattern of Epo and HIF-1α expression is a substantial contribution to the adaptive strategy of hypoxia tolerance in Spalax, evolved during 40 million years of evolution to cope with underground hypoxic stress.